(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Implementing effective environmental management for sustainable business is expressed in the integration of digital innovations, responsible sustainable practices, morals and motivation, environmental ethics, added value and recycling policies. The relevance of the topic is substantiated by the serious challenges modern businesses face regarding climate change, ecological sustainability, and social responsibility. The present study aims to prove that in the conditions of increasing public and corporate interest in environmental issues, organizations are brought to a growing need to adapt their business models by incorporating sustainability principles. Investors, regulators and consumers are directing their attention towards companies demonstrating commitment to environmental and social standards. The following research tasks have to be settled for reaching the above-mentioned goal: 1. to research the impact of the chemical industry on the environment; 2. to research the evolution of the way business is conducted; 3. to determine the extent of compliance of the business model of companies in the chemical industry with Sustainable Development Goals; 4. to identify new professions and roles in the context of environmental management for business needs. In the course of the study shall be justified the thesis that the combination of digital technologies, ethical principles and sustainability strategies provides Bulgarian companies in the chemical industry with the opportunity to adapt to current challenges, developing innovative business models, resp. meet regulatory requirements, create added value, competitive advantages and long-term sustainability. The methodology of questionnaire survey was used. The sample was formed by the method of random non-recurrent selection. The results of the research are expressed in the identification of best practices to serve as catalysts for balancing economic profitability and environmental responsibility. Additionally, innovative digital technologies to support businesses in environmental management, potential technological solutions to enhance the efficiency and sustainability of business processes and proposals for new professions and roles within the context of environmental management in enterprise practices are outlined.